Resistensi Tertutup Perempuan Jawa pada Budaya Patriarki pada Visual dan Komponen Film Kartini (2017) - Nurudin Sidiq Mustofa; Rony Ramadhan (Fakultas Ilmu Komputer Universitas Nahdlatul Ulama Sidoarjo, 2024)
Patriarchy, a system where men dominate, has long influenced society, including the notion that women are weaker. However, the spirit of resistance is increasingly echoed, including through media such as movies. This article aims to explore the traces of closed resistance to patriarchal culture in film, using the movie